7p-3=27p-10

Simple and best practice solution for 7p-3=27p-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7p-3=27p-10 equation:



7p-3=27p-10
We move all terms to the left:
7p-3-(27p-10)=0
We get rid of parentheses
7p-27p+10-3=0
We add all the numbers together, and all the variables
-20p+7=0
We move all terms containing p to the left, all other terms to the right
-20p=-7
p=-7/-20
p=7/20

See similar equations:

| -13=v=10-12 | | 2(4+w)=8+3w | | 8p-84=p | | 6/n=4/10 | | v+2/3=4(1/2) | | 36+4y-9=15y-13-3y | | -8(x+2)-8=-24 | | 4+1/2x=x-1 | | y(-3/4)=4(2/3) | | 3(5x+7)=-50+56 | | 8n+52=180 | | y-3/4=42/3 | | 41+5y-11=14y-12-2y | | 19=-k+9 | | 41+5y-11=14y-12 | | 8n+12+(−9)−(−6n)=n | | y-3/4=4(2/3) | | 42+5y-11=14y-12-2y | | -4+b=-11 | | 12+m=27 | | 4x-0.1=5x | | 2(5x=3)=14 | | 6y—1=1y | | 62-x=172 | | x^2=-8+4x | | 8=-5+12y | | -3-(1/4x)+3x=30 | | 2y+4=32y | | 6x-7=-4x-10 | | 4/9d+1/9=1/3 | | -3-(1/4x)+3=30 | | 9p+7=-4p-3 |

Equations solver categories